2017
DOI: 10.1177/2399808317733267
|View full text |Cite
|
Sign up to set email alerts
|

Architectural design creativity in Multi-User Virtual Environment: A comparative analysis between remote collaboration media

Abstract: Previous studies have argued that a Multi-User Virtual Environment has the potential to foster creative collaboration, but empirical studies that examine this claim are rare. With a focus on architectural design, this study has investigated the affordance of Multi-User Virtual Environment for the production of novel and appropriate solutions in remote collaborative environments. Forty-four participants produced design solutions using Multi-User Virtual Environment and online sketching in remote collaboration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The study found a slight decrease in creativity when using the virtual communication. In contrast, in another case study for architectural design [81] significant increases in the creativity scores were observed when using a multi-user virtual environment compared to using sketches.…”
Section: Communicationmentioning
confidence: 67%
“…The study found a slight decrease in creativity when using the virtual communication. In contrast, in another case study for architectural design [81] significant increases in the creativity scores were observed when using a multi-user virtual environment compared to using sketches.…”
Section: Communicationmentioning
confidence: 67%
“…Such multiple user virtual environments (MUVEs) allow users "to access virtual contexts, to interact with digital artifacts, to represent themselves through 'avatars,' (and) to communicate with other participants" [57]. From the planning and design collaboration perspective, MUVEs have been seen to support remote collaboration and education in architectural designing [56,58,59]. Moreover, collaborating while observing and visualizing other stakeholders' movements and design trials enhanced explorative creativity compared to working alone [59].…”
Section: Facilitating Remote Two-way Communicationmentioning
confidence: 99%
“…Systems developed for product design such as [45,50] usually implement shared 3D object manipulation, including viewing, changing and annotation of 3D objects. Remote collaboration systems are also popular in architectural design, where systems usually integrate the viewing of houses, rooms and furniture while allowing the users to discuss either via audio or integrated tools such as drawing in the virtual environment [51][52][53]. Many professional remote collaboration systems such as [54][55][56][57][58][59] typically include screen sharing and media sharing as interaction possibilities.…”
Section: Remote Collaborationmentioning
confidence: 99%